Integrated library systems. - Goldstein, C M (1983)
The development of integrated library systems is discussed. The four major discussion points are (1) initial efforts; (2) network resources; (3) minicomputer-based systems; and (4) beyond library automation. Four existing systems are cited as examples of current systems.